2021
DOI: 10.1016/j.lanwpc.2020.100072
|View full text |Cite
|
Sign up to set email alerts
|

Detachable string magnetically controlled capsule endoscopy for detecting high-risk varices in compensated advanced chronic liver disease (CHESS1801): A prospective multicenter study

Abstract: Background Gastroesophageal varices is a serious complication of compensated advanced chronic liver disease (cACLD). Primary prophylaxis to reduce the risk of variceal hemorrhage is recommended if high-risk varices (HRV) are detected. We performed this study to compare the accuracy, patients’ satisfaction and safety of detection of HRV by detachable string magnetically controlled capsule endoscopy (DS-MCCE) with esophagogastroduodenoscopy (EGD) as the reference. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…At present, indications for MCE examination do not include oesophageal disease and endoscopists could only describe the presentation of limited oesophageal pictures taken by the MCE in the final report. Previous studies provided the attachment of string to overcome the gravity and showed an increase in oesophageal examination time, improving diagnostic accuracy of oesophageal diseases [ 34 38 ]. The new method of detachable string MCE offers the possibility of complete viewing UGI and small intestine at one time.…”
Section: Discussionmentioning
confidence: 99%
“…At present, indications for MCE examination do not include oesophageal disease and endoscopists could only describe the presentation of limited oesophageal pictures taken by the MCE in the final report. Previous studies provided the attachment of string to overcome the gravity and showed an increase in oesophageal examination time, improving diagnostic accuracy of oesophageal diseases [ 34 38 ]. The new method of detachable string MCE offers the possibility of complete viewing UGI and small intestine at one time.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 , 19 ] However, this would be at a lower rate of spared EGDs than the ARP strategy, and most importantly, with a controversial rate of HRV missed above the accepted threshold of 5%. [ 20 , 21 , 22 , 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Another solution for the rapid esophageal transit issue is the detachable string magnetically controlled capsule endoscopy (also known as wireless magnetically controlled capsule endoscopy or WMCCE) which has been shown to be feasible and well tolerated in various studies[ 24 - 26 ]. A recent prospective multicenter study showed sensitivity of 92% and specificity of 80% for high-risk esophageal varices[ 27 ]. With regards to cost-effectiveness of ECE compared to traditional endoscopy, the results have been equivocal[ 28 - 30 ].…”
Section: Esophageal Capsule Endoscopymentioning
confidence: 99%